Impact of nutrient excess and endothelial nitric oxide synthase on the plasma metabolite profile in mice - Sansbury, Brian E.; Bhatnagar, Aruni; Hill, Bradford G. (Frontiers in Physiology, 2014)
An increase in calorie consumption is associated with the recent rise in obesity prevalence. However, our current understanding of the effects of nutrient excess on major metabolic pathways appears insufficient to develop safe and effective metabolic interventions to prevent obesity. Hence, we sought to identify systemic metabolic changes caused by nutrient excess and to determine how endothelial nitric oxide synthase (eNOS)—which has anti-obesogenic properties—affects systemic metabolism by measuring plasma metabolites. Wild-type (WT) and eNOS transgenic (eNOS-TG) mice were placed on low fat or high fat diets for 6 weeks, and plasma metabolites were measured using an unbiased metabolomic approach. High fat feeding in WT mice led to significant increases in fat mass, which was associated with significantly lower plasma levels of 1,5-anhydroglucitol, lysophospholipids, 3-dehydrocarnitine, and bile acids, as well as branched chain amino acids (BCAAs) and their metabolites. Plasma levels of several lipids including sphingomyelins, stearoylcarnitine, dihomo-linoleate and metabolites associated with oxidative stress were increased by high fat diet. In comparison with low fat-fed WT mice, eNOS-TG mice showed lower levels of several free fatty acids, but in contrast, the levels of bile acids, amino acids, and BCAA catabolites were increased. When placed on a high fat diet, eNOS overexpressing mice showed remarkably higher levels of plasma bile acids and elevated levels of plasma BCAAs and their catabolites compared with WT mice. Treatment with GW4064, an inhibitor of bile acid synthesis, decreased plasma bile acid levels but was not sufficient to reverse the anti-obesogenic effects of eNOS overexpression. These findings reveal unique metabolic changes in response to high fat diet and eNOS overexpression and suggest that the anti-obesity effects of eNOS are likely independent of changes in the bile acid pool.